Does synchronous endometrioid endometrial cancer have any prognostic effect on Stage I endometrioid ovarian cancer?. (May 2016) - Narin, M.A.; Karalok, A.; Basaran, D.; Ureyen, I.; Turkmen, O.; Turan, T.; Tulunay, G.
Abstract: Objective: To determine the effect of synchronous endometrial endometrioid cancer (SEEC) on the prognosis of patients with Stage 1 endometrioid ovarian cancer (EOC). Study design: Clinicopathological data of cases with Stage 1 EOC from January 2000 to November 2013 were retrieved from the computerized database of Etlik Zubeyde Hanim Women's Health and Research Hospital. Of the 31 patients included in the study, 15 patients had primary synchronous endometrial and ovarian cancer (SEOC) (Group 1) and 16 patients had EOC alone (Group 2). Results: Ovarian cancer substage and grade were compared between the two groups, and no significant differences were found. Most of the patients with SEEC had Grade 1 tumours ( n  = 13, 86.7%). In Group 1, nine (60.0%) patients had endometrial tumours with superficial myometrial invasion, and six (40.0%) patients had deep myometrial invasion. Median follow-up was 94 months. Ten-year disease-free survival rates were 92.9% for Group 1 and 84.6% for Group 2 ( p  = 0.565). Conclusion: Patients with Stage 1 EOC have excellent long-term survival. The presence of SEEC does not influence the prognosis of patients with Stage 1 EOC, even in the presence of deep myometrial invasion.